A Model for the Evaluation of Brazilian Road Transport: A Sustainable Perspective - Mariana Gonçalves de Carvalho Wolff; Marco Antonio Farah Caldas (Journal of Advanced Transportation)
Freight transportation in Brazil is heavily based on the road mode bringing heavy dependence of this mode to the country and some consequences such as high operating costs and high air emissions. For these reasons, it was considered the necessity of evaluating new investments made in this mode from a sustainable perspective, taking into account not only economic but also social and environmental concepts. Towards this purpose, the study develops an evaluation model of road transport infrastructure, the TIM, which will help decision making in situations of choice between different alternatives of road projects. The model includes ten variables that count from the initial investment in the road to air emissions of carbon dioxide. All are monetarized individually and then consolidated into a single equation. The result of applying the model is innovative when considering the three spheres of sustainability to evaluate future road transport projects and rank them.